The Effect of Job Satisfaction and Work Discipline on Teacher Performance at Buddhist Sunday Schools (SMB) of Guang Ji Indonesia in North Sumatra - Albert Albert; Shelly Susanti; Meriyawaty Amelia Prasetio; Kevin Putra Elbistian; Rivaldo Rivaldo; Cecilia Cecilia (Journal of Research in Social Science and Humanities, 2025)
Education plays a crucial role in shaping the quality of human resources in the era of global competition. Teachers are at the forefront of this process, as their performance directly determines the effectiveness of teaching and learning. This study examines the effect of job satisfaction and work discipline on the performance of teachers at Buddhist Sunday Schools (Sekolah Minggu Buddhis, SMB) under the Guang Ji Indonesia Buddhist Assembly in North Sumatra. A quantitative research method was employed, with data collected through questionnaires distributed to 106 respondents out of a population of 144 teachers, determined using the Slovin formula at a 5% significance level. The study analyzed three main variables: job satisfaction (X1), work discipline (X2), and teacher performance (Y). Regression analysis revealed that job satisfaction positively and significantly affects teacher performance (? = 32.641 + 0.686X1), while work discipline also exerts a positive and significant effect (? = 27.065 + 0.770X2). Furthermore, job satisfaction and work discipline jointly influence teacher performance (? = 25.832 + 0.266X1 + 0.509X2). These findings confirm that both individual and combined effects of job satisfaction and work discipline are essential in enhancing teacher performance. The results suggest that increasing teacher job satisfaction through fair compensation, career development, supportive leadership, and positive working conditions alongside fostering strong work discipline, can significantly improve the quality of teaching at Buddhist Sunday Schools. This study also highlights the importance of Buddhist ethical perspectives, which emphasize diligence, self-discipline, and commitment, in strengthening teacher professionalism.